Perancangan Sistem Penilaian Kinerja Karyawan - Raihan Rizky Nurfadila; T.M. Aditya Ramadhan; Amir Rozy Sinaga; Wasis Haryono (PT Pustaka Cendekia Group, 2025)
Employee performance assessment using Key Performance Indicators (KPI) is an effective method to measure individual contributions toward organizational goals. This report presents the development of a web-based application system that facilitates efficient KPI measurement, analysis, and reporting. The system features KPI data input, performance evaluation, and detailed reports for individual and team performance analysis. Testing results demonstrate that the application improves accuracy, transparency, and simplifies data-driven decision-making. With this system’s implementation, companies are expected to enhance employee performance and achieve strategic objectives optimally.